2017
DOI: 10.2147/ppa.s127612
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of care and strategies of self-management in patients with colorectal cancer

Abstract: PurposeGiven the inherent complexity of cancer care, in which personal, social, and clinical aspects accumulate and interact over time, self-management support need to become more comprehensive. This study has the following two aims: 1) to analyze and describe the complexity of individual patient situations and 2) to analyze and describe already established self-management strategies of patients to handle this complexity.MethodsA qualitative study was conducted. Ten focus groups were performed collecting persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
1
23
0
4
Order By: Relevance
“…The participants expressed concerns for patients who received an ostomy, noting that the ostomy represents substantial distress and a major treatment burden for patients. Managing an ostomy is among the consequences of CRC treatment adding to the complexity of the disease and requiring a proactive patient role [ 14 ]. According to Näsvall et al [ 41 ], in rectal cancer patients, an ostomy is found to affect quality of life through decreased physical and mental health functioning, increased fatigue and a distorted body image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants expressed concerns for patients who received an ostomy, noting that the ostomy represents substantial distress and a major treatment burden for patients. Managing an ostomy is among the consequences of CRC treatment adding to the complexity of the disease and requiring a proactive patient role [ 14 ]. According to Näsvall et al [ 41 ], in rectal cancer patients, an ostomy is found to affect quality of life through decreased physical and mental health functioning, increased fatigue and a distorted body image.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, patients with CRC must deal with many dimensions of burden during their treatment trajectory and must balance their demands and their capacity to self-manage [ 14 ]. This burden of treatment can be described as the extra work that health professionals (HPs) delegate to patients to live well with their chronic illness [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…All 10 studies investigating the value of SCPs were affirmative [25,76e84]. Most patients saw the benefits of SCPs and endorsed their addition to usual care; they felt empowered about having a plan that includes psychosocial elements [77,81,84]. GPs felt that SCPs were useful and enhanced their understanding of cancer diagnosis and treatment [76,83].…”
Section: Views Regarding Remote Follow-up and Survivorship Care Plansmentioning
confidence: 99%
“…The participants expressed concerns for patients who received an ostomy, noting that the ostomy represents substantial distress and a major treatment burden for patients. Managing an ostomy is among the consequences of CRC treatment adding to the complexity of the disease and requiring a proactive patient role [9]. According to Näsvall et al [38], in rectal cancer patients, an ostomy is found to affect quality of life through decreased physical and mental health functioning, increased fatigue and a distorted body image.…”
Section: The Burdens Of Surgical Treatment Of Colorectal Cancermentioning
confidence: 99%
“…Accordingly, patients with CRC must deal with many dimensions of burden during their treatment trajectory and must balance their demands and their capacity to self-manage [9]. This burden of treatment can be described as the extra work that health professionals (HPs) delegate to patients to live well with their chronic illness [10][11].…”
Section: Introductionmentioning
confidence: 99%